Seroepidemiology of Aino Virus in Farmed and Free-Ranging Cervids in the Republic of Korea - Yeh, Jung-Yong; Ga, Yun Ji (Frontiers in Veterinary Science, 2021)
Aino virus is an infectious, noncontagious, vector-borne agent that has been implicated in arthrogryposis-hydranencephaly syndrome in newborn cattle, sheep, and goats. Information about reservoirs and host animal species susceptible to Aino virus remains unclear. To further explore the role of cervids in Aino virus infection transmission, we investigated cervid sera to determine the prevalence of Aino virus-neutralizing antibodies and to identify factors correlated with antibody positivity. We screened cervid serum samples collected in the Republic of Korea to better understand infection patterns in this animal species. Overall, Aino virus infection was widespread; 75 of 716 (10.5%, 95% [95% CI] = 8.4–13.4) farmed-cervid serum samples collected from 292 herds contained antibodies to Aino virus. Serological evidence of Aino virus infection was demonstrated in 5 of 43 free-ranging cervids, accounting for a prevalence rate of approximately 11.6% (95% CI = 4.6–26.4). Our results revealed that age class and geographic location affected seroprevalence. The main risk factors associated with Aino virus seroprevalence were older age (> 2 years old, OR = 2.221, 95% CI = 1.209–4.079, P = 0.009 in adults), southern provinces (OR = 2.432, 95% CI = 1.445–4.093, P = 0.001), and western provinces (OR = 1.905, 95% CI = 1.041 – 3.488, P = 0.034). The results in this study suggest that cervid species might serve as important hosts for the transmission of Aino virus, highlighting the need for careful monitoring of Aino virus infections in cervids.